The Implementation of Enterprise Resource Planning Informatics Department Education Laboratory - Suratmanto, Bekti; Rahardjo Emanuel, Andi Wahju (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2024)
In preparing for the accreditation of units, study programs, and tertiary institutions to achieve a superior rating, Universitas Atma Jaya Yogyakarta (UAJY) often faces challenges in gathering and accessing the necessary resources. These difficulties stem from the accreditation preparation process, ineffective resource management, a lack of data integration, and restricted resource access. Taking advantage of advancements in information technology, UAJY has adopted the ERP Laboratory Information Management System (LIMS) to effectively manage the resources within its educational laboratories. These laboratories serve as a vital support unit in fulfilling the Tri Dharma of Higher Education and play a significant role in enhancing the learning process at the university. Enterprise Resource Planning (ERP) is a strategic tool that can provide organizations with a competitive edge by synchronizing, integrating, and optimizing data. The implementation of ERP LIMS serves as a solution for better resource management within the UAJY Informatics Department's educational laboratories.